Living with and dying from cancer: a humanities special study module. Issue 1 (1st June 2000) - Kirklin, Deborah; Meakin, Richard; Singh, Surinder; Lloyd, Margaret
Abstract : We describe a humanities-based, special studies module (SSM) exploring the impact of cancer on the lives of patients, families and professionals. Literature, film, art and drama provide third year medical undergraduates with vicarious experience of all of these perspectives in a format that has proved highly acceptable to students and tutors. The development, delivery, evaluation and evolution of this humanities-based course are described and we highlight some important elements of course organisation that emerged as being integral to its success.